EFEK HIPOLIPIDEMIK EKSTRAK ETANOL LIDAH BUAYA (Aloe vera L) PADA TIKUS PUTIH JANTAN MODEL HIPERKOLESTEROLEMIA - Devi Usdiana Rosyidah; Yustika Qasthari Primayanti; Oktein Satriyani (Biomedika, 2019)
Hyperlipidemia was a national health problem related to cardiovascular disease. The increasing public interest in natural materials as a management of hyperlipidemia research with natural ingredients. Aloe vera L. extract contained acemannan (glucomannan) and cellulose which could reduce lipid profiles. This aim of this study was to determine the effect of Aloe vera extract on the lipid profile of hypercholesterolemic modelling wistar male rats. This study used a laboratory experimental research design. The method was pre and post test with control group design. This study used 25 male Rattus norvegicus induced by high-fat feed for 14 days. Subjects were divided into 5 groups: negative control group (aquadest), positive control group (cholestiramine 0.2mg/200gBB/day), extract of Aloe vera L dose 0.3g/200gBB/day, extract of Aloe vera L dose 0.6g/200gBB/day, extract of Aloe vera L dose 1.2g/200gBB/day. Measurement of lipid profile levels was carried out on the 7th day, 21st day, and 35th day. Shapiro-Wilk test and Lavene test showed all data were normal and homogenous. The Paired t-Test results obtained p= 0,000. One Way Anova test with triglyceride showed p 0,05. The LSD test showed for the aquadest group triglyceride levels with 70% ethanol extract Aloe vera L dose 0.3g/200gBB/day, 0.6g/200gBB/day, and 1.2g/200gBB/day were p= 0.012, p= 0,000 and p= 0,000 respectively. Least significance different test for LDL cholesterol and total cholesterol in the aquadest group with 70% ethanol extract of Aloe vera L only at a dose of 1.2g /200gBB/day were significantly different with a value of p= 0.006 and p= 0.001. The conclusion was ethanol extract 70% Aloe vera L dose 1.2g/ 200gBB/day could reduce lipid profile such as triglyceride levels, LDL cholesterol and total cholesterol in hypercholesterolemic modelling wistar male rats.Keywords: Aloe Vera L., Lipid Profile, Glucomannan